2014
DOI: 10.1007/s11307-014-0764-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of VEGFR-2 Targeted Ultrasound Contrast Agent for the Early Evaluation of Response to Sorafenib in a Mouse Model of Hepatocellular Carcinoma

Abstract: BR55 appears to be useful in the prediction of response to sorafenib in a xenograft model of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 28 publications
1
31
0
1
Order By: Relevance
“…Among those imaging modalities ultrasound is advantageous due to its wide availability and relatively low cost allowing to perform repetitive exams during the course of treatment, in particular during the early course of treatment, to assess whether early changes of imaging signal may be predictive of treatment response. With the use of molecularly targeted contrast microbubbles, 2D USMI has been shown to be feasible for monitoring tumor anti-angiogenic treatment (13,14). However, one of the major limitations of 2D USMI in monitoring tumor response compared to whole body imaging modalities such as CT, MRI, or PET is the limited field of view only representing a small fraction of the imaged tumor volumes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those imaging modalities ultrasound is advantageous due to its wide availability and relatively low cost allowing to perform repetitive exams during the course of treatment, in particular during the early course of treatment, to assess whether early changes of imaging signal may be predictive of treatment response. With the use of molecularly targeted contrast microbubbles, 2D USMI has been shown to be feasible for monitoring tumor anti-angiogenic treatment (13,14). However, one of the major limitations of 2D USMI in monitoring tumor response compared to whole body imaging modalities such as CT, MRI, or PET is the limited field of view only representing a small fraction of the imaged tumor volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound molecular imaging (USMI) using contrast microbubbles targeted at molecular markers expressed on the tumor neovasculature is emerging as a promising tool to assess expression levels of angiogenic markers such as VEGFR2 for earlier cancer detection (912) and monitoring anti-angiogenic therapy (13,14). USMI combines the advantages of ultrasound such as relatively low cost, wide availability and portability, and lack of ionizing radiation with those of molecular imaging to allow quantitative monitoring of disease processes at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…UMI has also proven its ability to detect biomarkers of early response to chemotherapy in several cancer types by MBs targeted to single biomarker expressions (VEGFR2, a V b 3 , endoglin, Annexin V, or VEGF-VEGFR complex) [24,[166][167][168][169] and MBs targeted to two or more of these biomarker expressions [142]. Impressively, studies have shown that UMI using a v b 3 -tMBs is a consistent method that can classify a tumour as a responder or a non-responder as early as two days after treatment [170,171].…”
Section: In Vivo Molecular Imagingmentioning
confidence: 99%
“…Indeed, potentially non-immunogenic targeted microbubbless have been developed (BR55 ® ; Bracco Imaging, Switzerland). So far, the only human applications include an experimental phase 0 study on prostate cancer, but preclinical results are very promising [69], especially in the field of response to antiangiogenic treatment. However, once approved for clinical use, molecular CEUS may improve HCC diagnosis or residual activity detection after locoregional treatments, widening the horizons of CEUS.…”
Section: Guidance and Evaluation Of Hcc Treatmentsmentioning
confidence: 99%